Property and maintenance management framework for New Zealand's state schools: a thesis presented in partial fulfilment of the requirements for the degree of Doctor of Philosophy in Construction at Massey University, Albany, New Zealand - Le, An Thi Hoai (Massey University, 2021)
School buildings and infrastructure are considered fundamental elements of any community. The buildings and infrastructure are not only supposed to provide a pleasant, and safe environment for staff and students, but they are also a clearly visible presentation of the education system. As a result, it is important to ensure that school properties are well maintained through proactive management. In New Zealand (NZ), state school properties are owned by the Ministry of Education (MoE) and managed and operated by the school board of each school with the assistance of external consultants. This research aims to develop a framework which helps those involved in managing school buildings and infrastructure in New Zealand's state schools by focusing on improving the collaboration among the key stakeholders. Previous research on managing existing property and associated theoretical concepts, such as asset management, property management, maintenance management, stakeholders’ involvement, and maturity model frameworks, were reviewed to identify research problems. In order to refine the research objectives, a preliminary study was conducted that involved the researcher attending training courses on property and maintenance management to understand processes, make connections, conduct interviews with other attendees, and distribute a survey among them. Findings from the preliminary study highlighted the central role of stakeholders’ collaboration for the provision of efficient property and maintenance management, but other issues were also identified. A further in-depth study based on interviews with school managers was undertaken to cover the current activities and processes, challenges, roles, and responsibilities of the key stakeholders in managing existing buildings and infrastructure in state schools in New Zealand. Based on findings from the literature review and interviews, a maturity assessment model was developed, and a questionnaire was distributed to explore the maturity levels of different management processes currently in place with the aim of identifying the priorities for process improvement actions. The maturity level scores revealed the most needed improvement areas that the key stakeholders should focus on, including the reporting system, performance evaluation, staff training, lesson sharing, communication, and continuous improvement. In addition, Partial Least Squares Structural Equation Modelling (PLS-SEM) approach was used to explore the relationships among key stakeholders and test the research hypotheses. The results of PLS-SEM assessment prove that there are undeniable relationships between the key stakeholders. This also highlighted that all stakeholders are responsible to work closely as a team as they have both direct and indirect effects on each other's performance. Close teamwork contributes to the overall outcome of property and maintenance management for NZ's state schools. A property and maintenance management framework for NZ's state schools was then developed based on the findings of the literature review, and data analysis using the key concepts of the Plan-Do-Check-Act cycle. The proposed framework comprises five stages (Establish, Plan, Implement, Evaluate, and Improve - E-PIE-I, and shortened to PIE) and includes activities in each stage. More activities were added in the Establish phase in order to address the need to provide staff training programmes and improve the collaboration between people involved in the processes. Moreover, the proposed PIE features a feedback loop in the Evaluate and Improve stages which helps assess performance of the processes and obtain feedback and learning outcomes for continuous improvements. Validation interviews with school managers were conducted and the results show that the PIE framework could help improve the property and maintenance management for New Zealand's state schools. The research contributes to the property and maintenance management field with a focus on the collaboration between the people involved in the process. The research also reveals other challenges and issues in managing school property in state schools and proposes solutions to overcome these challenges. More importantly, this research produces a set of diagrams in the PIE framework which can be used as guidelines for school managers and other stakeholders to perform their roles effectively. The study finally produces recommendations for improvements in managing school property at both the school and the MoE level. The findings should be of interest to top management, schools, service providers, and researchers dealing with the management of existing buildings and infrastructure in schools.
Keywords: School plant management; School buildings; Maintenance and repair; New Zealand; 330299 Building not elsewhere classified